The Effect of E-Learning Based Learning on the Learning Achievement of Class IX Students in Social Sciences in MTs Muhammadiyah Wuring - Ayuwandira, Ayuwandira; Chotimah, Nur (Holistic Science, 2023)
This study aims to determine the effect of e-learning-based learning on the learning achievement of class IX students in social studies subjects at MTs Muhammadiyah Wuring. The formulation of the problem in this study is whether there is an effect of e-learning-based learning on the learning achievement of class IX students in social studies subjects at MTs Muhammadiyah Wuring. The purpose of this study is to the effect of e-learning-based learning on the learning achievement of grade IX students in social studies subjects at MTs Muhammadiyah Wuring. This type of research is quantitative descriptive research. The data source in this study consists of population and samples. Data collection techniques using questionnaires/questionnaires, variables and documentation. Data analysis techniques used by researchers in this study include: instrument tests and validity tests. Based on the results of the research concluded: Based on the results of the analysis described, the results were obtained that e-learning-based learning variables had a positive and significant effect on learning achievement variables. This is evidenced by the value of tcount of 2,454> from the Ttable 2,022 and the SIG value. equal to 0.019 at the Sig level 0.05. So, 0.019 <0.05 means that e-learning-based learning variables affect learning achievement variables. From the results of this study it can be seen that based on the descriptive analysis level the material can be updated itself at a very high value proven by an average score of 87% while the descriptive analysis level makes it easier to learn at a high value as evidenced by an average score of 80%